"FROM LOVEBIRDS TO BROKEN HEARTS: THE IDIOMS OF LOVE AND ROMANCE" (Лучшие интеллектуальные исследования, 2024)
Love has been a central theme in languages and cultures around the world for centuries, often expressed in the form of idioms. These idioms reflect the various stages, emotions, and complexities of romantic relationships, from the initial spark of "love at first sight" to the deep connections symbolized by phrases like "match made in heaven." By understanding and using love idioms, language learners and native speakers alike can convey intricate feelings in powerful, relatable ways. This article explores twenty popular idioms of love, examining their meanings and how they are used in context to express the profound impact of love on human experiences.